Bilateral Cancer in Prostate Biopsy Associates with the Presence of Extracapsular Disease and Positive Surgical Margins in Low Risk Patients: A Consideration for Bilateral Nerve Sparing Radical Prostatectomy Decision - Sfoungaristos, Stavros; Perimenis, Petros (Urology Journal, 2013)
Purpose: To evaluate the epidemiological, clinical and pathological parameters that may predict the presence of positive surgical margins and extraprostatic disease in patients with low risk [prostate specific antigen (PSA) < 10, and Gleason score ≤ 6, stage T1c)] prostate cancer. Materials and Methods: We retrospectively analyzed the medical records of patients who had undergone radical prostatectomy from January 2005 until January 2011. The analysis comprised patients’ age, preoperative serum prostate specific antigen (PSA) level, prostate volume, PSA density, biopsy Gleason score, the presence of bilateral disease according to the results of biopsy cores analysis, the percentage of cancer in biopsy material and the presence of high grade prostatic intraepithelial neoplasia. Results: A total of 117 patients were included in the study. Positive surgical margins were found in 37 (31.6%) patients and 23 (19.7%) had advanced disease. The results of the multivariate analysis showed that bilateral disease was the single significant predictor for advanced disease prediction (P = .04). Same results was obtained by the univariate analysis of the variables for prediction of positive surgical margins, where bilateral disease after biopsy cores analysis was the only factor to be statistical significant (P = .018). Conclusion: Bilateral prostate cancer in prostate biopsy is significantly associated with positive surgical margins and advanced disease in patients that are operated for prostate cancer of low risk. This observation may assist the selection of patients in whom a bilateral nerve sparing radical prostatectomy is planned to be performed.